Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.130.038.1993
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Water and Bulk Calcite Chemistry, Leg 130, and Calcite Recrystallization

Abstract: We investigated minor element ratios (Sr/Ca and Mg/Ca) in bulk sediment samples from Sites 803-807 using a recently optimized sample treatment protocol for calcium-carbonate-rich sediments consisting of sequential reductive and ion exchange treatments. We evaluated this protocol relative to bulk sediment leaching using samples from Sites 804 and 806, the two end-member sites in the depth transect, reporting as well Mn/Ca and Fe/Ca ratios for sediments from these two sites processed by means of both methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…9). Delaney & Linn (1993) suggested that the formation of celestite could explain the concurrent decline in sulphate and stabilization of Sr in the pore water, but no celestite was observed in the present study, so at least the main part of the dissolved Sr is taken up by barite. Cronan (1974) cited authors reporting up to 3% Sr in solid solution in microcrystalline barite in deep-sea sediments.…”
Section: Recrystallizationmentioning
confidence: 43%
See 1 more Smart Citation
“…9). Delaney & Linn (1993) suggested that the formation of celestite could explain the concurrent decline in sulphate and stabilization of Sr in the pore water, but no celestite was observed in the present study, so at least the main part of the dissolved Sr is taken up by barite. Cronan (1974) cited authors reporting up to 3% Sr in solid solution in microcrystalline barite in deep-sea sediments.…”
Section: Recrystallizationmentioning
confidence: 43%
“…During recrystallization, calcite releases Sr (Baker et al, 1982;Delaney & Linn, 1993) and approaches stable crystal shape, a process which is largely over for sediments of Palaeogene age (Figs 4, 6 and 9). The released Sr precipitates as a component in barite (Fig.…”
Section: Recrystallizationmentioning
confidence: 99%
“…The average calcite Mg content of deep samples (>800 mbsf) is 0.032 ± 0.002 molal while the Mg content of the entire section at 807A ranges between 0.022 and 0.048 molal. The Mg contents of calcite at 807 show no significant or systematic changes with depth that would support the use of a model in which the solid Mg content varied (Delaney and Linn, 1993). For each of the reference K Mg values, we calculate K Mg as a function of pore fluid Ca concentration in each time step of the model (Fig.…”
Section: Model For Neogene Seawater Mg Concentration Changesmentioning
confidence: 99%
“…The maximum r-error in the Sr concentration measurements is 2% (Delaney and Linn, 1993); thus the r value assigned for the minimization of v 2 is equal to the maximum error, or 0.02 AE y i . In order to match the model data to measured data prior to minimization, the measured data are linearly interpolated to the 25-meter grid spacing of the model.…”
Section: The Time-dependent Depositional Modelmentioning
confidence: 99%
“…Although much of past research has focused on isotopic records, a growing literature on elemental variation has led to a better understanding of variability of elements like Sr (e.g., Graham et al, 1982;Renard, 1986;Delaney and Boyle, 1988;Baker et al, 1990;Delaney and Linn, 1993;Hampt and Delaney, 1997;Andreasen and Delaney, 2000a). Despite the effort focused on Sr, as pointed out by Andreasen and Delaney (2000b), significant scatter and differences exist in these records.…”
Section: Mj Malone Data Report: Geochemistry Of Fine Fraction Carbomentioning
confidence: 99%